Hubungan Tingkat Pengetahuan Tentang ISPA dengan Perilaku Pencegahan ISPA pada Masyarakat di Wilayah Kerja Puskesmas Sukomulyo Kabupaten Gresik - Zufra Inayah; Sestiono Mindiharto; Syifa Fazia Hanifaturohmah; Iswania Hesti Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2026)
The health problem that is currently a problem in the public health aspect is Acute Respiratory Infection (ARI) because the incidence rate is quite high. Better preventive behavior can affect the level of public knowledge about the disease. This study was carried out to analyze the relationship between the level of knowledge about ISPA and preventive behavior in the community in the working area of the Sukomulyo Health Center, Gresik Regency. This study applied a quantitative approach to cross sectional design. A total of 100 respondents were selected using a simple random sampling technique, then tested using the Fisher's Exact Test. The results of the analysis showed that the majority of respondents with a high level of knowledge also applied good preventive behavior, which was 91.0%. In contrast, 59.1% of respondents with a low level of knowledge showed poor preventive behavior. The p< value of 0.001 indicates a meaningful relationship between the level of knowledge of ISPA and its prevention behavior. This research study proves that there is an increase in public knowledge which can be an important weapon to support efforts to prevent ISPA and become the basis for health centers to strengthen education programs on an ongoing basis.